Pediatric penile reconstruction using autologous split-thickness skin graft. Issue 3 (June 2016) - Diaz, E.C.; Corcoran, J.F.; Johnson, E.K.
Summary: This video provides a case report of penis entrapment secondary to excessive skin removal during circumcision. It highlights the technical aspects of pediatric penile reconstruction using autologous split-thickness skin graft (STSG). Key points include: 1. Infection prevention is paramount and antibiotic prophylaxis is routine. 2. The usual harvest site for the STSG is the lateral thigh because of its source of glabrous skin and convenient proximity to the penis. The lateral thigh is also outside of the diapered area, which helps lessen postoperative pain and infectious risks. 3. A dermatome is used to harvest the STSG. Skin thickness for penis coverage at this age is usually 10-12/1000 of an inch. 4. Direct contact of the graft and wound bed is essential for graft uptake. Hemostasis of the wound bed is critical to prevent hematoma formation. Elimination of redundant tissue is also important to ensure maximal contact between the graft and underlying wound bed. 5. A pressure dressing or bolster is used to prevent shear, and provide contact between the graft and wound bed for at least the first 5 days. 6. A semi-occlusive dressing, Tegaderm, was used on the donor site and it is believed that it provides a moist environment conducive for epithelial and dermal healing. 7. Lymphedema can result if excess distal penile skin is not excised. It is prudent to limit the amount of mucosal collar or consider direct anastomosis to the glans.